Pavement Road Crossing Sirtu Village Kondowa - Rumbayan, Hendra Kundrad Susanto; Musrifin; Sijono; Faty M, Qiber Azim (Lembaga Riset dan Inovasi Masyarakat Madani, 2023)
Based on its geographical position, Pasarwajo District has regional boundaries, namely: Kapontori District, Wolowa District, Wabula District, South Buton Regency, Flores Sea and BauBau City. Kondowa Village is one of the villages in Pasarwajo District whose population is mostly transmigration. The area of Pasarwajo District is 3.77 KM2. Kondowa Village only has 1 access road to connect with Holimombo Jaya Village so the community took the initiative to build a new road that will be an alternative route to go to the opposite village. The results of the debate resulted in the design of the Kondowa Village Road and the materials that will be used for the construction of the village road which is then agreed upon with the length of the road to be worked on, which is 2,715 meters long. The Kondowa Village Government hopes to collaborate with the Civil Engineering Study Program, Faculty of Engineering, University of Muhammadiyah Buton to continue helping design planning in the building industry.